Α1 Antitrypsin and the prevalence and severity of asthma. Issue 3 (20th February 2004) - von Ehrenstein, O S; Maier, E M; Weiland, S K; Carr, D; Hirsch, T; Nicolai, T; Roscher, A A; von Mutius, E
Abstract : In a random sample of children (aged 9–11 years; n = 5629), who were studied according to the ISAAC phase II protocol, heterozygosity of the α1 antitrypsin (α1 -AT) Pi genotypes MS or MZ, or low α1 -AT plasma levels, were not associated with an increased risk of developing asthma. Asthmatics with low levels of α1 -AT were particularly prone to develop airway hyperresponsiveness and reduced lung function.